THE ROLE OF ACADEMIC LEADERSHIP IN IMPROVING STUDENT RETENTION IN THE FACULTY OF ECONOMICS, UNIVERSITY OF NIAS - Pasti Okto Anugerah Gulo; Delipiter Lase; Meiman Hidayat Waruwu; Fatolosa Hulu (LPPM YPITI, 2026)
This study aims to analyze the role of academic leadership in improving student retention at the Faculty of Economics, Nias University. The high number of inactive and absent students indicates serious challenges in the management of academic services and leadership effectiveness within the faculty. The research approach used was descriptive qualitative with a phenomenological method. Data were collected through in-depth interviews, observations, and documentation involving key informants such as the dean, vice dean, head of study program, academic advisors, students, and alumni. The results show that academic leadership at the Faculty of Economics, Nias University, has a significant influence on student retention through three main mechanisms: (1) strengthening academic communication and coordination, (2) personal guidance and mentoring of students through academic advisors, and (3) creating a participatory and supportive academic climate. However, limitations in the intensity of academic guidance and the low capacity of lecturers to provide psychosocial support to students are still found. Factors such as economic constraints, low learning motivation, and limited facilities also worsen the retention rate. This study recommends the application of transformational and visionary leadership styles, strengthening the academic guidance system, and implementing data-based policies to monitor the risk of dropout early. The results of this study are expected to be a basis for faculties in designing academic leadership strategies that are oriented towards increasing student retention and academic success.